Factors associated with county‐level mental health during the COVID‐19 pandemic. Issue 5 (30th December 2021) - Lupton‐Smith, Carly; Badillo‐Goicochea, Elena; Chang, Ting‐Hsuan; Maniates, Hannah; Riehm, Kira E.; Schmid, Ian; Stuart, Elizabeth A.
Abstract: The objective of this study is to determine county‐level factors associated with anxiety, depression, and isolation during the coronavirus disease 2019 (COVID‐19) pandemic. This study used daily data from 23, 592, 355 respondents of a nationwide Facebook‐based survey from April 2020 to July 2021, aggregated to the week‐county level to yield 212, 581 observations. Mental distress prevalences were modeled using weighted linear mixed‐effects models with a county random effect. These models revealed that weekly percentages of mental distress were higher in counties with higher unemployment rates, populations, and education levels; higher percentages of females, young adults, individuals with a medical condition, and individuals very worried about their finances and COVID‐19; and lower percentages of individuals who were working outside the home, living with children, without health insurance, and Black. Anxiety peaked in April 2020, depression in October 2020, and isolation in December 2020. Therefore, United States counties experienced the mental health effects of the pandemic differently dependent upon their characteristics, and mental distress prevalence varied across time.